SOCIALIZATION OF HANDLING RUMINANT LIVESTOCK AFTER FLASH FLOODS IN SOUTHEAST ACEH IN 2025 - Muttaqinullah; Joharsah; Hadirin; Kartono; Sudarma JA; Ilham Alsi; Carli (CV. Naskah Aceh, 2026)
Southeast Aceh Regency is one of the regencies in Aceh Province, characterized by mountainous terrain and many rivers, which often leads to disasters such as floods and landslides, resulting in flash floods in several areas of Southeast Aceh Regency. Socialization activities related to livestock management during floods are considered necessary to raise awareness among farmers and encourage cooperation in handling livestock during floods. This community service activity is carried out in three general stages: the preparation stage, the discussion stage, and the site survey stage. The discussion methods used are socialization and Focus Group Discussion (FGD) to understand the community's responses and management in flood-prone areas. The implementation of these activities contributes to increasing the knowledge and understanding of the community regarding river flood management. Armed with the knowledge and understanding provided, it is expected that the community's behavior patterns regarding the management of river border areas, waste, and so on can be applied and have a positive impact on improving river management by the community.